The Impact of New Yogyakarta International Airport (NYIA) Development for Economic Growth in Special Region of Yogyakarta - Suparmono Suparmono (Telaah Bisnis, 2019)
Abstract Development plan of New Yogyakarta International Airport (NYIA) in Kulon Progo District developed based on Airport City concept, has expected could be growth center and new regional development in Kulon Progo District and it can push development region in around. The New Yogyakarta International Airport planned have capacity of 28 aircraft and 11 avio bridge. The Airport designed with runway 5,400 meters, and able to accommodate large bodied aircraft. Terminal will be expanded can accommodate around 24 million passangers per year. Development of New Yogyakarta International Airport Access is estimated requires 5,087 trillion rupiah. Beside of road support, development of railway also planned to increase access towards new airport. The new growth center has expected that region become a city of its own and can evolve to become the equity of growth between district in Special Region of Yogyakarta. By use analysis tools of input output (I-O Analysis), this article purposes to analyze the impact of New Yogyakarta International Airport (NYIA) for economic growth in Special Region of Yogyakarta.